Media Multitasking in Younger and Older Adults: Associations with Cognitive Abilities and Biological Stress Responses - Wannagat, Wienke; Martin, Tamara; Nieding, Gerhild; Rohleder, Nicolas; Becker, Linda (Media Psychology, 2024)
Media multitasking is increasingly common in everyday life and can be a stressful experience, especially for older adults. The current study investigated the effects of media multi- vs. single-tasking on both task performance and biological as well as subjective stress responses in an experimental laboratory setting based on a scenario that closely replicated the demands of a multitasking situation, in which a strenuous and repetitive primary task was interrupted by relevant messages that require attention. We examined differences in media multitasking performance and associated stress between younger (18–35 years) and older (65–85 years) adults, and differences in cognitive abilities as a potential explanation for expected age-related differences in media multitasking. The findings suggested lower task performance in the multitasking condition in both age groups. The older adults showed even higher multitasking costs, but we found no evidence of lower cognitive abilities as an explanation of this effect. Media multitasking was not found to elicit greater stress responses (biological or subjective) than single-tasking. However, the results indicate that older adults have a greater biological stress response (salivary α-amylase) than younger adults when working on a computer under time pressure, regardless the task requirements (single- or multitasking).
CRIS-Team Scopus Importer:2024-03-29